EFEKTIVITAS KEBIJAKAN PENDANAAN PEMBANGUNAN HUTAN TANAMAN RAKYAT (HTR) - Iis Alviya; Fentie J Salaka; M Zahrul Muttaqin; Fitri Nurfatriani; Elvida Y Suryandari (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2020)
Community Plantation Forest, known as Hutan Tanaman Rakyat or HTR, is one of social forestry programs aiming at reducing economic inequality at rural community level. However, there is no evidence that HTR has improved the community welfare at the local level due to some problems particularly funding availability. This study aims to evaluate the effectiveness of financing policy in developing HTR carried out by the Public Service Agency of the Ministry of Environment and Forestry (BLU-KLHK) and to look for alternative sources of funding that might support the ongoing funding mechanism. Survey and focus group discussion (FGD) are methods used to collect the data. Qualitative descriptive, content analysis and Grindle theory approaches are implemented to analyze data. The results show that, based on the content of the policy, HTR financing mechanism managed by BLU-KLHK is efficient, comprehensive and prudent in regulating and facilitating the financial support to develop HTR. However, this funding policy has not been effective to support HTR business development at the implementation stages. Some other funding schemes that might be potential to support the development of HTR include LPDB, SBSN, Rural Area Development Program, and Village Fund.